1985
DOI: 10.1159/000233874
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Freund’s Adjuvant Treatment on Mast Cell Histamíne Release and Homocytotropic Antibody Synthesis

Abstract: The present study examines the influence of Freund’s complete adjuvant (FCA) injections on sensitized PVG rats with respect to (1) serum levels of IgE and IgG antibodies and total IgE (all assessed by radioimmunoassays) and (2) the capacity of serosal mast cells to release histamine on challenge in vitro with ‘immunological’ secretagogues (specific antigen, anti-IgE, concanavalin A) or with compound 48/80. The rats were immunized with 10 μg ovalbumin (OA); alum, Bordetella pertussis vaccine, or si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…A strong and selective inhibitory effect of preinoculation of CFA on IgE anti-OVA production was noted by Smith and Butchko (29) in both high-or moderate-responder mice . The difference in our results may be attributable to differences in timing of administration of CFA and antigen, which was shown to be a critical factor in one system investigated (30) .…”
Section: Resultscontrasting
confidence: 59%
“…A strong and selective inhibitory effect of preinoculation of CFA on IgE anti-OVA production was noted by Smith and Butchko (29) in both high-or moderate-responder mice . The difference in our results may be attributable to differences in timing of administration of CFA and antigen, which was shown to be a critical factor in one system investigated (30) .…”
Section: Resultscontrasting
confidence: 59%
“…The early inflammation induced by CFA has been shown to be mast cell–dependent. 25 The mechanism of itch induced by CFA in the acute phase should be investigated further. We found that BK dose-dependently evoked scratching responses in the CFA-inflamed area.…”
Section: Discussionmentioning
confidence: 99%
“…This was apparently not due to a nonspecific effect of FGA since responsiveness of the cells to compound 48/80 or to anti-IgE was not affected (13), and an analogous treatment with FCA of animals immunized with Silica gel, if anything, decreased mast cell responsiveness to antigen (13). Even more unexpectedly, if animals to be immunized with OA together with Perthydra] were treated with FCA 1 week before immunization, they had lower IgE-antibody levels but higher mast cell responsiveness to OA (but not to ConA or 48/ 80) than saline-treated eontrols 3 weeks after immunization (13). Thus, one can modulate, by suitable FCA-treatment of animals, serosal mast cell responsiveness to antigen and OA-IgE-antibody serum levels in opposite direetions.…”
Section: Thirdly If Mast Cell-sensitizint; Ige-type Antibodies Were mentioning
confidence: 91%
“…We have examined ihe correlation between serosal mast eell, lung, and tracheal tissue responsiveness lo aniigen and scrum OA-lglv aniilKKly levels in seveial ral .sitain.s (10,12,13). Tlie lader vat'iablc wa.s examined by iaclitjiiiununt)a.s.say in solid pha.sc performance, utilizing reagenis prepared wilh th<' aid ol myeloma proieins (7, .…”
Section: Thirdly If Mast Cell-sensitizint; Ige-type Antibodies Were mentioning
confidence: 99%
See 1 more Smart Citation